(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
The economic and political relationship between the United States and China has been characterized by growing tensions, particularly under the Trump and Biden administrations. This paper applies game theory to model the complex dynamics of the US-China trade war, focusing on protectionism, currency devaluation, and negotiations as key strategies in the ongoing dispute. With both countries engaging in tariff imposition, currency manipulation accusations, and retaliatory measures, the paper examines the implications of these strategies through a currency war and trade war game model. The findings suggest that while protectionism may escalate into a trade war, it is a less catastrophic outcome compared to currency devaluation, which can lead to a global currency war with far-reaching economic consequences. This study underscores the importance of strategic decisions in international trade, highlighting the risks associated with both protectionist measures and competitive currency devaluation. Ultimately, it proposes that effective negotiation and strategic protectionism can prevent further economic destabilization, providing a way out of the escalating tensions between the US and China.